2018
DOI: 10.1177/1740774518770648
|View full text |Cite
|
Sign up to set email alerts
|

The US Food and Drug Administration’s expedited approval programs: Evidentiary standards, regulatory trade-offs, and potential improvements

Abstract: The US Food and Drug Administration has several regulatory programs and pathways to expedite the development and approval of therapeutic agents aimed at treating serious or life-debilitating conditions. A common feature of these programs is the regulatory flexibility, which allows for a customized approval approach that enables market authorization on the basis of less rigorous evidence, in exchange for requiring postmarket evidence generation. An increasing share of therapeutic agents approved by the Food and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 63 publications
2
55
0
Order By: Relevance
“…Although expedited programs differ in their scope and focus, which range from putting deadlines on regulatory review times to approving products on the basis of earlier-stage data than what is typically required, their shared objective is to provide faster access to new products. 28 One rationale for introducing such programs is to meet patient demand for potentially effective therapies for life-threatening diseases for which there is no existing treatment. 29,30 Studies have confirmed that drugs that qualify for expedited programs have shorter development times and receive regulatory approval faster.…”
Section: Expedited Programsmentioning
confidence: 99%
“…Although expedited programs differ in their scope and focus, which range from putting deadlines on regulatory review times to approving products on the basis of earlier-stage data than what is typically required, their shared objective is to provide faster access to new products. 28 One rationale for introducing such programs is to meet patient demand for potentially effective therapies for life-threatening diseases for which there is no existing treatment. 29,30 Studies have confirmed that drugs that qualify for expedited programs have shorter development times and receive regulatory approval faster.…”
Section: Expedited Programsmentioning
confidence: 99%
“…Contributing to this may be the varying quality of clinical trial evidence available at the time of approval and resulting uncertainty around the extent of clinical benefit. 27 28 29 As more evidence accumulates after approval, the assessment of therapeutic value may also evolve.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we appreciated Dr. Woodcock's clarification that all New Drug Applications 'are required by law to contain all information and studies that sponsoring companies have conducted or are aware of.' 8 The language we used in our review, suggesting that 'it is possible that drug sponsors only submit individual trials with the largest treatment effects to the FDA', 1 was poorly worded.…”
Section: Clarifications and Commentsmentioning
confidence: 99%
“…13 We agree that trial participants should reflect the population of patients that are expected to benefit from the therapeutic agent being evaluated. 1 However, it is also worth noting that precision medicine enables drugs to be approved for narrower indications based on smaller trials. While these more 'precise' approvals can effectively address unmet medical needs, there are potential concerns as well if the drugs are then prescribed for broader indications, beyond those formally evaluated by the FDA.…”
Section: Clarifications and Commentsmentioning
confidence: 99%